Associations between ground reaction forces and barbell accelerations in weightlifting - Kipp, K.; Harris, C. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to investigate associations between vertical ground reaction forces and vertical barbell accelerations during the snatch. Barbell kinematic and force plate kinetic data were collected during a weightlifting competition. Time-series data were normalized to 100% of lift phase and were entered into a pattern recognition algorithm that extracted principal patterns and calculated principal pattern scores. Significant associations indicate that a smaller, and temporally shorter, decrease in ground reaction forces during the transition phase is associated with a smaller decrease in barbell acceleration during the transition phase and a smaller peak barbell acceleration during the second pull phase. In order to optimize barbell acceleration, weighlifters may need to ensure a quick transition between the first and second pull.